Microstructure, oxidation behaviour and thermal shock resistance of self-passivating W-Cr-Y-Zr alloys. (August 2020) - Sal, Elisa; García-Rosales, Carmen; Schlueter, Karsten; Hunger, Katja; Gago, Mauricio; Wirtz, Marius; Calvo, Aida; Andueza, Iñigo; Neu, Rudolf; Pintsuk, Gerald
Highlights: Zr addition to W-Cr-Y alloys results in grain refinement and nanoparticle dispersion. Oxidation behavior of W-Cr-Y is slightly improved by Zr addition. ELM-like loading on HTed Zr-containing alloy results in no cracking or damage. Abstract: Self-passivating tungsten based alloys for the first wall armor of future fusion reactors are expected to provide an important safety advantage compare to pure tungsten in case of a loss-of-coolant accident with simultaneous air ingress, due to the formation of a stable protective scale at high temperatures in presence of oxygen preventing the formation of volatile and radioactive WO3 . In this work, Zr is added to self-passivating W-10Cr-0.5Y alloy, manufactured by mechanical alloying and HIP, in view of improving its mechanical strength and thus, its thermal shock resistance. The as-HIPed W-10Cr-0.5Y-0.5Zr exhibits a nanocrystalline microstructure with the presence of an extremely fine nanoparticle dispersion. After heat treatment at 1555 °C for 1.5 h, the grain size growths from less than 100 nm to 620 nm and nanoparticles are present both at the grain boundaries and inside the grains. Oxidation tests at 1000 °C revealed that the alloy with Zr exhibits also a strong oxidation reduction compared to pure W. The long-term oxidation rate is similar to that of the alloy without Zr. Under thermal shock loading simulating 1000 ELM-like pulses at the divertor, the heat treated Zr-containing alloy did not present any damage.